2006
DOI: 10.1057/palgrave.emr.1500062
|View full text |Cite
|
Sign up to set email alerts
|

People are strange when you're a stranger: senior executives select similar successors

Abstract: Despite Sweden being considered one of the most equality‐minded countries, the uppermost organizational levels are so male dominated that mandatory board of director gender quotas are considered. Homogeneity may only be decreased with difficulty, as it arises through basic social mechanisms such as homosocial reproduction, that is, people prefer and, therefore, recruit people who are similar to themselves. Present structure is perpetuated. Previous research suggests that such reproduction occurs on an organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…ISCO1 were less likely than the PPE to have a service class I parent or reproduce social position, perhaps due to the many lower grade occupations within the category. These results support the views that Swedish corporate directors are traditionally recruited from a small pool, often being the sons of the existing corporate classes (Stafsudd 2006) and the political elite is drawn from parents with a stratification position higher than the overall population but lower than other advantaged groups (Hansson 2013). Unlike the UK, Sweden possesses evidence of Glastonbury style recruitment, with greater social closure for the PPE.…”
Section: <Table 3 About Here>supporting
confidence: 73%
See 1 more Smart Citation
“…ISCO1 were less likely than the PPE to have a service class I parent or reproduce social position, perhaps due to the many lower grade occupations within the category. These results support the views that Swedish corporate directors are traditionally recruited from a small pool, often being the sons of the existing corporate classes (Stafsudd 2006) and the political elite is drawn from parents with a stratification position higher than the overall population but lower than other advantaged groups (Hansson 2013). Unlike the UK, Sweden possesses evidence of Glastonbury style recruitment, with greater social closure for the PPE.…”
Section: <Table 3 About Here>supporting
confidence: 73%
“…Sweden, for instance, is often portrayed as having corporate boardrooms governed by a fraternity of older men and their sons (Stafsudd 2006;Jonnergård and Stafsudd 2011), imposing glass ceilings limiting women from higher positions (Albrecht et al 2003) and forming a separate power block to political elites (Rydgren 2005), although such distinctions are dwindling (Bohman et al 2012;Edling et al 2014). This tradition of passing governance to sons, and separation of business and state, perhaps originates from the development of Swedish corporations traditionally growing from small, local businesses rather than large, multiple ownership (Glete 1989), with power and influence continuing to operate at localised levels (Edling et al 2014).…”
mentioning
confidence: 99%
“…In the Nordic countries, the shareholders not only formally appoint directors but also play a bigger role in the selection process and-when holding a large ownership share-they themselves hold a board seat. Past studies, however, show that the nomination committee often proposes prospective candidates based on recommendations by current board members or by executive search firms that tend to follow the directors' preferences (Johnson et al 2011;Stafsudd 2006). Anecdotal evidence and case-based evidence from Nordic firms similarly suggest that the decision to search for a female candidate is often initiated by the board.…”
Section: Hypothesis 1bmentioning
confidence: 99%
“…The small amount of research on the selection of directors has consistently found tokenism and dominant male homophily (the preference for associating with like people). 84 Female representation on boards has, globally, stagnated at the 15 per cent level on average, and tokenism is a basic response to external pressures. Director selection based on homophily is an important element in board composition.…”
Section: Selecting Board Members -Direction Of Targets or Quotasmentioning
confidence: 99%